2008
DOI: 10.1057/palgrave.jibs.8400353
|View full text |Cite
|
Sign up to set email alerts
|

From servicescape to consumptionscape: a photo-elicitation study of Starbucks in the New China

Abstract: A servicescape can be viewed as the frozen potential of a consumptionscape, which is unleashed when consumers “twist” the resources of its built environment for their own purposes. In this paper we explore how young, urban Chinese consumers transform the iconic global brand Starbucks into a consumptionscape through their enactment of personally meaningful experiences, roles, and identities in the setting. We employ the qualitative research methodology of photo-elicitation by having consumers record their exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
89
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 23 publications
4
89
1
1
Order By: Relevance
“…Despite the Forbidden City controversy, Starbucks has on the whole been enthusiastically received in China: since first opening in Beijing in 1999, there are now more than 400 Starbucks coffee shops, and the brand outperforms its US parent (Taipei Times, 2009, cited in Lin, 2012. Starbucks is a potent symbol of the 'new' China, popular among the middle class and young adults and a common feature of upscale shopping malls and gentrified neighbourhoods (Han & Zhang, 2009;Lin, 2012;Venkatraman & Nelson, 2008). However, the meaning of foreign brands -and Starbucks specifically -for middleclass Chinese consumers is by no means transparent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the Forbidden City controversy, Starbucks has on the whole been enthusiastically received in China: since first opening in Beijing in 1999, there are now more than 400 Starbucks coffee shops, and the brand outperforms its US parent (Taipei Times, 2009, cited in Lin, 2012. Starbucks is a potent symbol of the 'new' China, popular among the middle class and young adults and a common feature of upscale shopping malls and gentrified neighbourhoods (Han & Zhang, 2009;Lin, 2012;Venkatraman & Nelson, 2008). However, the meaning of foreign brands -and Starbucks specifically -for middleclass Chinese consumers is by no means transparent.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Chinese consumers may perceive a foreign brand as the 'glocal' site (imagined or otherwise) of intersection between the local and the global/foreign/Western (e.g. Lin, 2012;Venkatraman & Nelson, 2008).…”
mentioning
confidence: 99%
“…Today, the Chinese marketplace is posited to become one of the largest consumer markets in the world, and this provides tremendous growth opportunities for international products and brands. Young Chinese consumers were selected because they represent the ''New China consumer '' (Venkatraman and Nelson, 2008). Further, they form a major part of the lucrative ''global consumer segment'' (Anderson and He, 1998;Quelch, 1999;Hung et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, it seems valuable for future research to elaborate on the issue if photographing in-store experiences can distort participants' actual experiences, since people do not usually takes photographs of themselves or their experiences while going to a store. However, Venkatraman & Nelson (2008) already have indicated that there is no evidence that people, enrolled in photographing their proper experiences, distorted their experiences in a particular way. Fourthly, after have experimented with digital as well as non-digital photography, the researchers are clear proponents of digital photography.…”
Section: Resultsmentioning
confidence: 99%